Sustained exposure to abscisic acid enhances the colonization potential of the mutualist fungus Piriformospora indica on Arabidopsis thaliana roots - Pes̆kan-Berghöfer, Tatjana; Vilches-Barro, Amaya; Rausch, Thomas (The new phytologist, 2015)
Root colonization by the beneficial fungus Piriformospora indica is controlled by plant innate immunity, but factors that channel this interaction into a mutualistic relationship are not known. We have explored the impact of abscisic acid (ABA) and osmotic stress on the P. indica interaction with Arabidopsis thaliana. The activation of plant innate immunity in roots was determined by measuring the concentration of the phytoalexin camalexin and expression of transcription factors regulating the biosynthesis of tryptophan-related defence metabolites. Furthermore, the impact of the fungus on the content of ABA, salicylic acid, jasmonic acid (JA) and JA-related metabolites was examined. We demonstrated that treatment with exogenous ABA or the ABA analogue pyrabactin increased fungal colonization efficiency without impairment of plant fitness. Concomitantly, ABA-deficient mutants of A. thaliana (aba1-6 and aba2-1) were less colonized, while plants exposed to moderate stress were more colonized than corresponding controls. Sustained exposure to ABA attenuated expression of transcription factors MYB51, MYB122 and WRKY33 in roots upon P. indica challenge or chitin treatment, and prevented an increase in camalexin content. The results indicate that ABA can strengthen the interaction with P. indica as a consequence of its impact on plant innate immunity. Consequently, ABA will be relevant for the establishment and outcome of the symbiosis under stress conditions.